2018
DOI: 10.1161/circheartfailure.118.005629
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Regional Adipose Tissue Distribution and Risk of Heart Failure Among Blacks

Abstract: Background: Obesity is highly prevalent among blacks and is associated with a greater risk of heart failure (HF). However, the contribution of regional adiposity depots such as visceral adipose tissue (VAT) and abdominal subcutaneous adipose tissue toward risk of HF in blacks is unknown. Methods and Results: We included 2602 participants (mean age: 59 years, 35% men) from the Jackson Heart Study without prevalent HF who underwent computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
2
25
0
1
Order By: Relevance
“…Rao et al reported a significant effect of BMI, WC and CT‐measured visceral adipose tissue (VAT) on the risk of HFpEF in a longitudinal manner in black, white, Hispanic and Chinese‐American subjects 52 . Pandey et al found no association between higher VAT and risk of HF amongst blacks 53 . Thus, the relationship between body composition and diastolic dysfunction may differ amongst different ethnicities.…”
Section: Discussionmentioning
confidence: 97%
“…Rao et al reported a significant effect of BMI, WC and CT‐measured visceral adipose tissue (VAT) on the risk of HFpEF in a longitudinal manner in black, white, Hispanic and Chinese‐American subjects 52 . Pandey et al found no association between higher VAT and risk of HF amongst blacks 53 . Thus, the relationship between body composition and diastolic dysfunction may differ amongst different ethnicities.…”
Section: Discussionmentioning
confidence: 97%
“…The role of obesity in pathogenesis of HF, and particularly HFpEF, has drawn greater attention. 10,19,23,105 While anthropometrics are commonly used to categorize obesity at present, they are not always representative of excess regional adiposity. 38 Focus on quantifying regional distribution of adiposity may provide more insight into incidence and disease progression of an obese HFpEF phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which CRF and regional fat depots mediate HF risk are not well established, prior studies have reported epidemiological associations between CRF, visceral adiposity (VAT), and abnormal cardiac remodeling patterns. VAT has been associated with higher left ventricular (LV) mass and lower LV end diastolic volume (EDV) [ 5 , 9 ], while CRF has been associated with higher LV filling pressures and diastolic dysfunction [ 10 , 11 ]. These cardiac remodeling patterns may reflect intermediate phenotypes in the progression from at-risk to clinical HF [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…LV peak systolic circumferential strain (E cc ) is a sensitive marker of abnormal cardiac remodeling and is independently associated with risk of HF [ 14 , 15 ]. CRF and regional adiposity have each been associated with impairment in E cc independent of BMI [ 5 , 16 ]. However, prior studies have not examined the association between regional fat distribution and subclinical myocardial dysfunction, independent of CRF, a potential confounder not accounted for in prior reports.…”
Section: Introductionmentioning
confidence: 99%